“Fair” Status of Marriage Wali According to Shafi'i Mazhab and Hanafi Mazhab - Fadhil Mubarak; Januddin Januddin (Al Mashaadir : Jurnal Ilmu Syariah, 2022)
This research is motivated by the existence of a marriage carried out by a virtuous wali in a society where the majority adhere to the Shafi'i school of thought. The purpose of this research is to find out what the opinion of the Shafi'i and Hanafi schools is about the just status of marriage wali today, and find out how the opinion of the Syafi'i and Hanafi schools compares the status of marriage wali. This research is library research. Data analysis method used comparative method. The object of this study is the comparison of the Syafi'i and Hanafi schools regarding fair wali as a condition for the validity of a marriage contract. In addition, KHI does not require that wali in marriage must be fair. The Syafi'i school of thought explains that the requirements for a wali are fair with six criteria, namely Islam, puberty, sound mind, independence, male and fair. When viewed from the opinion of the Shafi'i school of thought, the implementation of marriage by a virtuous wali, the marriage is void. However, Islamic law is not rigid. Even though according to Islamic law the marriage of a person whose wali is wicked is void, there is still a loophole for his child's marriage to remain valid according to Islamic law. By following the opinion of other scholars such as the Hanafi school of thought, the marriage is still valid with the following reasons; First, namely, someone's Islam is considered sufficient to become a marriage wali, so it doesn't look at whether the person is fair or not. The two wicked wali may become wali, namely looking at the element of benefit for others.